Association between CYP2D6 Genotypes and the Risk of Antidepressant Discontinuation, Dosage Modification and the Occurrence of Maternal Depression during Pregnancy - Bérard, Anick; Gaedigk, Andrea; Sheehy, Odile; Chambers, Christina; Roth, Mark; Bozzo, Pina; Johnson, Diana; Kao, Kelly; Lavigne, Sharon; Wolfe, Lori; Quinn, Dee; Dieter, Kristen; et al. (Frontiers in Pharmacology, 2017)
Importance: Polymorphic expression of drug metabolizing enzymes affects the metabolism of antidepressants, and thus can contribute to drug response and/or adverse events. Pregnancy itself can affect CYP2D6 activity with profound variations determined by CYP2D6 genotype. Objective: To investigate the association between CYP2D6 genotype and the risk of antidepressant discontinuation, dosage modification, and the occurrence of maternal CYP2D6, Antidepressants, Depression during pregnancy. Setting: Data from the Organization of Teratology Information Specialists (OTIS) Antidepressants in Pregnancy Cohort, 2006–2010, were used. Women were eligible if they were within 14 completed weeks of pregnancy at recruitment and exposed to an antidepressant or having any exposures considered non-teratogenic. Main Outcomes and Measures: Gestational antidepressant usage was self-reported and defined as continuous/discontinued use, and non-use; dosage modification was further documented. Maternal depression and anxiety were measured every trimester using the telephone interviewer-administered Edinburgh Postnatal Depression Scale and the Beck Anxiety Inventory, respectively. Saliva samples were collected and used for CYP2D6 genotype analyses. Logistic regression models were used to calculate crude and adjusted odds ratios (OR) with 95% confidence intervals. Results: A total of 246 pregnant women were included in the study. The majority were normal metabolizers (NM, n = 204, 83%); 3.3% (n = 8) were ultrarapid metabolizers (UM), 5.7% (n = 14) poor metabolizers (PM), and 8.1% (n = 20) intermediate metabolizers (IM). Among study subjects, 139 women were treated with antidepressants at the beginning of pregnancy, and 21 antidepressant users (15%) discontinued therapy during pregnancy. Adjusting for depressive symptoms, and other potential confounders, the risk of discontinuing antidepressants during pregnancy was nearly four times higher in slow metabolizers (poor or intermediate metabolizers) compared to those with a faster metabolism rate (normal or ultrarapid metabolizers), aOR = 3.57 (95% CI: 1.15-11.11). Predicted CYP2D6 metabolizer status did not impact dosage modifications. Compared with slow metabolizers, significantly higher proportion of women in the fast metabolizer group had depressive symptom in the first trimester (19.81 vs. 5.88%, P = 0.049). Almost 21% of treated women remained depressed during pregnancy (14.4% NM-UM; 6.1% PM-IM). Conclusions and Relevance: Prior knowledge of CYP2D6 genotype may help to identify pregnant women at greater risk of antidepressant discontinuation. Twenty percent of women exposed to antidepressants during pregnancy remained depressed, indicating an urgent need for personalized treatment of depression during pregnancy.